A cross-sectional study of point-of-care lactate testing in integrated community care management (ICCM) for children with acute respiratory illness in rural uganda - Matte, Michael; Koyama, Natsumi; Giandomenico, Dana; Baguma, Emmanuel; Kibaba, Georget; Ntaro, Moses; Reyes, Raquel; Mulogo, Edgar M; Boyce, Ross M; Ciccone, Emily Jxx (My University, 2024)
Abstract Background Integrated community case management (iCCM) programs leverage lay village health workers (VHWs) to carry out the initial evaluation of children with common conditions including malaria, pneumonia and diarrhea. Therefore, it is imperative that VHWs are able to identify children who are critically ill and require referral to a health facility. Elevated venous lactate levels have been associated with severe illness and adverse health outcomes, including death. However, lactic acidosis may not be recognized in rural settings because it is not routinely measured outside of hospitals and research studies. Point-of-care lactate tests may help identify patients in need of a higher level of care and improve VHWs’ ability to make timely and appropriate referrals. Methods The study was a cross-sectional evaluation of children aged <5 y presenting to VHWs in rural southwestern Uganda with complaints of fever and cough. Demographics, clinical presentation, evaluation, management and disposition were recorded. VHWs were trained and instructed to perform lactate testing using a point-of-care assay in eligible participants. Results During the study period, 238 children were enrolled and completed an initial assessment. Of the 204 participants included in the analysis, 113 (55.4%) were female, and the median (IQR) age was 23 (9–36) months. Most participants, 139/200 (69.5%), had negative results on the malaria rapid diagnostic test. The median lactate level was 2.1 mmol/L; 12% (24/204) had a lactate ≥3.5 mmol/L and only nine participants (4.4%) had a lactate ≥5 mmol/L. Having a lactate level above either cut-off was not associated with the presence of danger signs at presentation. Conclusions Few children presenting with fever and cough to VHWs in western Uganda had elevated lactate levels. However, most of the children with elevated lactate levels did not otherwise satisfy established iCCM criteria based on physical examination findings for referral to a health facility. Therefore, while elevated lactate was not associated with danger signs in this small study, it is possible that there is under-recognition of severe illness using current iCCM guidelines.